An Investigation into Emergency Planning Requirements and Challenges of Disaster Management in the Kingdom of Saudi Arabia - Alrehaili, Naif Rashed (TDMRC, Universitas Syiah Kuala, 2021)
Every year, the Kingdom of Saudi Arabia (KSA) is exposed to different natural hazards. However, flash floods have been the most common hazard during the previous few decades. Between 2000 and 2020, over 1,000 people lost their lives from flash floods, resulting in an economic loss amounting to billions of US dollars. By focusing on flash floods, a systematic review of the extracted data was conducted. They were analyzed based on the suitability of their content and data for emergency planning requirements and disaster management challenges in the KSA. A total of 104 articles, papers, and plans were reviewed, of which only 18 complete papers met the inclusion criteria, including one plan and the General Directorate of Civil Defense (GDCD) website. The author has concluded that: 1) the essential requirements for emergency planning in the KSA include: conducting studies that show potential natural hazards, their locations, and their implications, and taking appropriate measures that reduce the possible causes of natural hazards; 2) The challenges facing the disaster management in the KSA are: lack of policies; the ambiguity of legislation and plans; poor coordination between stakeholders; lack of databases. This is the first investigation into emergency planning requirements and challenges of disaster management in the KSA. Furthermore, a scientific consensus predicts an increase in the frequency and magnitude of flash floods in the KSA. Therefore, the gaps need to be addressed in order to reduce the impact on inhabitants and infrastructure.